A Survey of Examination Malpractice in The West African Senior School Certificate Examination (WASSCE) in The Central Region of Ghana - Yeboah, Abraham (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The purpose of the study was to examine examination malpractice in the West African Senior School Certificate Examination (WASSCE) in the Central Region of Ghana. Specifically, the study sought to examine the prevalence of malpractice in the WASSCE and which people were involved in the malpractice. Methods and Materials: A descriptive survey with quantitative methods of data collection was used for the study. The target population for students and teachers was 5500 and 500, respectively. Purposive and random sampling techniques were used to select 408 students and 138 teachers for the study. Researchers-designed questionnaires were used as the instrument for data collection. Descriptive statistics (frequencies, percentages, means and standard deviations) were used for the data analysis. Findings: It was found that teachers perceived the prevalence of examination malpractice to be high whilst students perceived it to be low. The study showed that the people who are predominately involved in examination malpractice in WASSCE are students followed by teachers and invigilators. Conclusions: It is recommended that external invigilators and supervisors other than teachers should be employed during May/June WASSCE and that WAEC should privatize the security of the examination papers so that the company would be held responsible for any leakage.